1995
DOI: 10.1016/0895-7061(95)00216-2
|View full text |Cite
|
Sign up to set email alerts
|

24-h ambulatory blood pressure in 352 normal Danish subjects, related to age and gender*

Abstract: Normal values for ambulatory blood pressure are presented in a randomly selected age- and gender-stratified population. Differences between office blood pressure and ambulatory blood pressure increased with age suggesting that the previously observed higher blood pressure seen in the elderly partly might be explained by a greater impact of white coat hypertension in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
237
5
7

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(276 citation statements)
references
References 21 publications
27
237
5
7
Order By: Relevance
“…This limit is somewhat higher than reported by others; the explanation for this can-apart from the different methodologies-rely on the different populations studied, eg, unlike in mediterranean countries 2 the 'siesta effect' is not discernible in the 24-h BP profiles in the northern European countries. 17 If one accepts the cut-off criterion as suggested from our data, the prevalence of white coat hypertension is approximately 19% among patients with newly diagnosed mild-to-moderate hypertension, a somewhat lower figure than previously reported, 6 but similar to the figures reported by others. 29 It is obvious, though that the frequency of white coat hypertension is declining with more severe office BP elevations at admission, as is illustrated in Table 3, where 135.6/90.4 mm Hg is the cut-off criterion (definition #3 from Table 2).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This limit is somewhat higher than reported by others; the explanation for this can-apart from the different methodologies-rely on the different populations studied, eg, unlike in mediterranean countries 2 the 'siesta effect' is not discernible in the 24-h BP profiles in the northern European countries. 17 If one accepts the cut-off criterion as suggested from our data, the prevalence of white coat hypertension is approximately 19% among patients with newly diagnosed mild-to-moderate hypertension, a somewhat lower figure than previously reported, 6 but similar to the figures reported by others. 29 It is obvious, though that the frequency of white coat hypertension is declining with more severe office BP elevations at admission, as is illustrated in Table 3, where 135.6/90.4 mm Hg is the cut-off criterion (definition #3 from Table 2).…”
Section: Discussionsupporting
confidence: 86%
“…As part of a multicentre study to establish the distribution of ABP in the population, 17 we performed 24-h BP monitoring in subjects drawn at random from the Danish national register. There was an intended similar number of subjects in different gender and age strata from 20-79 years.…”
Section: Methodsmentioning
confidence: 99%
“…1 On the other hand, studies investigating the relationship between age and ambulatory BP have yielded conflicting findings, ranging from no change in BP to moderately higher BP as a function of age. [2][3][4][5][6][7] The relationship between gender and age-related BP changes is unclear, as most studies do not report on the association between these variables. In a meta-analysis of 23 ambulatory studies including subjects between the ages of 17-80, Staessen and colleagues 8 reported that SBP increases on the average 2.8 mm Hg per decade in women, but only 0.2 mm Hg per decade in men, whereas DBP increases 1.1 mm Hg per decade in both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] The 'white coat effect' can be easily detected as well as white coat hypertension. It has been shown that subjects with ISH are characterised by a higher variability of BP, high prevalence of white coat effect and postprandial fall.…”
Section: Epidemiologymentioning
confidence: 99%